Heat shrinkage resistant waterproof coating and preparation method thereof

By using specific formulas and preparation methods in heat-resistant coatings, the coating heat shrinkage problem caused by the demanding length of polyester fibers is solved, and the coating shrinkage performance and waterproof effect are maintained over a wider range, avoiding bubbles, Wrinkle and rupture phenomenon.

CN118725727BActive Publication Date: 2025-01-17FOSHAN ZHAOJING ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410994219.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-01-17
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

Existing heat-resistant coatings have strict requirements on polyester fiber lengths, making it difficult to ensure that the length of polyester fibers is within the range of 380-420μm in industrial production, resulting in bubbling, wrinkling and cracking of the coating during heat shrinkage.

Method used

Adopt a heat-shrink waterproof coating formula, including water-based acrylic modified polyurethane resin, quartz, easily dispersed modified magnetic powder, hollow glass beads, mannitol, polyether modified polysiloxane, polyester fiber, titanium dioxide modified bamboo charcoal , Heat-shrink modified nanocellulose and deionized water, through specific stirring steps and preparation methods, ensure that the coating maintains shrinkage performance during the heat shrinkage process and adapts to the error of the length of polyester fibers.

Benefits of technology

It effectively avoids bubbles, wrinkles and cracks during the heat shrinkage process, and maintains waterproof performance, expands the applicability of the polyester fiber length range, and improves the feasibility of industrial production of coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005144908160000061
    Figure GDA0005144908160000061
  • Figure GDA0005144908160000071
    Figure GDA0005144908160000071
Patent Text Reader

Abstract

The invention relates to a coating, in particular to a heat shrinkage resistant waterproof coating and a preparation method thereof; the heat shrinkage resistant waterproof coating comprises an A component: 100-130 parts of waterborne acrylic modified polyurethane resin, 10-20 parts of quartz, 5-10 parts of easily dispersible modified magnetic powder, 5-10 parts of hollow glass beads, 1-3 parts of mannitol and 2-4 parts of polyether modified polysiloxane; and a B component: 15-20 parts of polyester fiber, 15-20 parts of titanium dioxide modified bamboo charcoal, 1-1.5 parts of heat shrinkage modified nano cellulose, 2-4 parts of sodium tripolyphosphate and 30-40 parts of deionized water; the polyester fiber is used to provide the coating with the necessary shrinkage performance when the base surface is heat shrunk, and the heat shrinkage modified nano cellulose is used to further improve the shrinkage rate of the coating during the heating process, so as to compensate for the reduced shrinkage performance of the coating when the length error of the polyester fiber is large, thereby making the heat shrinkage coating have a wider selection range for the polyester fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coating, in particular to a heat shrinkage resistant waterproof coating and a preparation method thereof. Background Art

[0002] Recent studies have found that adding polyester fibers to heat-resistant coatings can effectively improve the tensile strength of the coating after curing, that is, the coating after adding polyester fibers can shrink accordingly with the shrinkage of the substrate, and the coating can still show shrinkage performance even when the substrate temperature far exceeds the hot melting temperature of the polyester fibers. In addition, the study also found that the length of the added polyester fibers has an important influence on the shrinkage effect. When the length is about 400μm, the coating is not prone to bubbling, wrinkling and rupture when exposed to heat.

[0003] At present, the polyester fiber size requirements for heat shrink coatings are very stringent, generally a single filament diameter of 15-30μm and a length of 380-420μm. The single filament diameter can be accurately set by the extrusion die, but the current industrial production of such short shreds is mechanical shredding after extrusion. Limited by the accuracy of mechanical equipment, the shredded length has an error of more than 10μm, and the high shrinkage rate of short fibers (generally 10-20%) causes the length of polyester fibers to change during storage and transportation. In actual industrial production, it is difficult to ensure that the feed length does not exceed 380-420μm, and it is difficult to promote its use. There is an urgent need for a heat shrinkage-resistant waterproof coating with a wide range of restrictions on the length of polyester fibers. Summary of the invention

[0004] In view of the deficiencies in the prior art, one of the objects of the present invention is to provide a heat-shrinkage-resistant waterproof coating, which will not have bubbling, wrinkling and cracking after the base surface is heat-shrunk; the second object of the present invention is to provide a preparation method of the heat-shrinkage-resistant waterproof coating; the third object of the present invention is to provide a construction method of the heat-shrinkage-resistant waterproof coating.

[0005] One of the purposes of the present invention is achieved through the following technical solutions:

[0006] A heat shrinkage resistant waterproof coating, comprising the following raw materials in parts by weight:

[0007] Component A: 100-130 parts of water-based acrylic modified polyurethane resin, 10-20 parts of quartz (400 mesh), 5-10 parts of easily dispersible modified magnetic powder, 5-10 parts of hollow glass beads (10-30 μm), 1-3 parts of mannitol and 2-4 parts of polyether modified polysiloxane;

[0008] Component B: 15-20 parts of polyester fiber, 15-20 parts of titanium dioxide modified bamboo charcoal (200 mesh), 1-1.5 parts of heat-shrinkable modified nanocellulose, 2-4 parts of sodium tripolyphosphate and 30-40 parts of deionized water.

[0009] Preferably, the polyester fiber has a diameter of 15-30 μm and a length of 300-350 μm or 450-500 μm.

[0010] Preferably, the method for preparing the easily dispersible modified magnetic powder comprises the following steps:

[0011] Step 1: weigh deionized water, ferrous chloride, ferric chloride and sericin according to a weight ratio of 100:6.35:4.05:3-3.5 and stir to mix evenly to obtain a mixed solution and keep stirring to prevent precipitation and aggregation;

[0012] Step 2: Adjust the pH of the mixture to 12 and stir at 60°C for 4 hours;

[0013] The third step is to adjust the pH of the mixed solution to 7 during stirring and then dry it at 120° C. into powder to obtain easily dispersible modified magnetic powder.

[0014] Traditional magnetic powder (ferroferric oxide) is easy to aggregate and difficult to disperse due to its magnetic properties. Now, through protein modification, an organic film is attached to its surface, making it easier to disperse in water or glue. The principle of protein modification is: sericin is dissolved in warm water, and a large amount of amino groups released react with ferrous chloride and ferric chloride to generate ferroferric oxide and water when heated. The excess part of sericin adheres to ferroferric oxide as it dries and loses its water solubility due to high temperature, becoming a permanent protective film of ferroferric oxide. Then, a ferroferric oxide flame retardant material with simple process and easy dispersion is obtained.

[0015] Preferably, the method for preparing titanium dioxide modified bamboo charcoal comprises the following steps:

[0016] The first step is to weigh titanium dioxide, dispersant and bamboo charcoal fiber according to a weight ratio of 4-7:3:100;

[0017] Step 2: Add 10 times the total weight of titanium dioxide, dispersant and bamboo charcoal fiber in water, stir evenly and filter to obtain a pressed cake;

[0018] The third step is to crush and sieve the pressed cake to obtain titanium dioxide modified bamboo charcoal in powder form.

[0019] Preferably, the method for preparing the heat-shrinkable modified nanocellulose comprises the following steps:

[0020] The first step is to weigh nanocellulose, 20wt% sodium hydroxide aqueous solution, ethylene glycol, glucomannan (KGM), 2,3-epoxypropyltrimethylammonium chloride and sodium carboxymethyl starch in a weight ratio of 4:1:5:1:1:1;

[0021] Step 2: Mix nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol and glucomannan, and stir at 60° C. for 1 h to obtain a primary mixed solution;

[0022] Step 3: Add 2,3-epoxypropyltrimethylammonium chloride to the primary mixed solution and stir for 1 hour at 60°C to obtain a secondary mixed solution;

[0023] Step 4: add sodium carboxymethyl starch to the second mixed solution, stir at 50° C. for 1 hour, wash with excess ethylene glycol until neutral, filter and dry to obtain heat-shrinkable modified nanocellulose.

[0024] The second object of the present invention is achieved by the following technical solutions:

[0025] A method for preparing a heat shrinkage resistant waterproof coating comprises the following steps:

[0026] S1 weighs the water-based acrylic modified polyurethane resin, quartz, easily dispersible modified magnetic powder, hollow glass beads, mannitol and polyether modified polysiloxane in the formula amount of component A;

[0027] S2: stirring the water-based acrylic modified polyurethane resin at a speed of 20-30 r / min, adding mannitol first and then adding the remaining raw materials in component A in small amounts and multiple times during the stirring process, and after the feeding is completed, increasing the speed to 250-500 r / min and stirring for 5-10 minutes to obtain a composition A, which is sealed and stored for later use;

[0028] S3 weighs the polyester fiber, titanium dioxide modified bamboo charcoal, heat-shrinkable modified nanocellulose, sodium tripolyphosphate and deionized water in the B component;

[0029] S4: Stir deionized water at a speed of 200-250 r / min, and add sodium tripolyphosphate, heat-shrinkable modified nanocellulose, titanium dioxide modified bamboo charcoal and polyester fiber in sequence during the stirring process, with an interval of 1 min for each raw material. After the feeding is completed, increase the speed to 250-500 r / min and stir for 5-10 min to obtain a B composition, which is sealed and stored for later use.

[0030] The third object of the present invention is achieved by the following technical solutions:

[0031] A construction method for a heat shrinkage resistant waterproof coating comprises the following steps:

[0032] Step 1: Stir the B composition at a speed of 20-30 r / min, add the A composition in small amounts several times during the stirring process, increase the speed to 250-500 r / min and stir for 2-3 minutes after the addition is completed, and finally increase the speed to 1000 r / min and stir for 2-3 minutes to obtain a coating; the A and B compositions cannot be mixed in advance, because the water-based acrylic modified polyurethane resin is an organic emulsion, and oil-water stratification may occur after long-term storage after adding water and mixing, and adjusting as needed can better ensure the quality of the coating;

[0033] Step 2: Apply the coating evenly on the surface of the heat shrink tube;

[0034] Step three: Place at room temperature for 7 days and the construction is completed.

[0035] Preferably, the coating thickness is 100-150 μm. Since the heat shrink tube itself is very thin and needs to be easy to shrink, the thickness is reduced as much as possible while ensuring coverage.

[0036] The beneficial effects of the present invention are as follows: polyester fibers are used to provide the coating with the necessary shrinkage properties when the base surface is heat-shrunk, and heat-shrinkable modified nanocellulose is used to further improve the shrinkage rate of the coating during the heating process, so as to compensate for the reduced shrinkage performance of the coating when the polyester fiber length error is large, thereby making the heat-shrinkable coating have a wider range of polyester fiber selection. DETAILED DESCRIPTION

[0037] The following is further described in conjunction with specific implementation methods:

[0038] Example 1

[0039] The preparation of easily dispersible modified magnetic powder comprises the following steps:

[0040] Deionized water, ferrous chloride, ferric chloride and sericin were weighed in a weight ratio of 100:6.35:4.05:3 and stirred to obtain a mixed solution, which was kept stirred to prevent precipitation and aggregation; the pH of the mixed solution was adjusted to 12 and stirred at 60° C. for 4 hours; during stirring, the pH of the mixed solution was adjusted to 7 and then dried at 120° C. into a powder to obtain easily dispersible modified magnetic powder.

[0041] The method for preparing titanium dioxide modified bamboo charcoal comprises the following steps:

[0042] Titanium dioxide, dispersant and bamboo charcoal fiber are weighed according to a weight ratio of 4:3:100; water 10 times the total weight of titanium dioxide, dispersant and bamboo charcoal fiber is added, stirred evenly and filtered to obtain a pressed cake; the pressed cake is crushed and sieved to obtain titanium dioxide modified bamboo charcoal in powder form.

[0043] The preparation of heat-shrinkable modified nanocellulose comprises the following steps:

[0044] Nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol, glucomannan, 2,3-epoxypropyltrimethylammonium chloride and sodium carboxymethyl starch were weighed in a weight ratio of 4:1:5:1:1:1; nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol and glucomannan were mixed, and stirred at 60°C for 1 hour to obtain a primary mixed solution; 2,3-epoxypropyltrimethylammonium chloride was added to the primary mixed solution, and the solution was stirred at 60°C for 1 hour to obtain a secondary mixed solution; sodium carboxymethyl starch was added to the secondary mixed solution, and the solution was stirred at 50°C for 1 hour, and the excess ethylene glycol was washed until neutral, and the solution was filtered and dried to obtain heat-shrinkable modified nanocellulose.

[0045] The preparation of heat shrinkage resistant waterproof coating comprises the following steps:

[0046] S1 weighed 100 parts of waterborne acrylic modified polyurethane resin, 10 parts of quartz, 5 parts of easily dispersible modified magnetic powder, 5 parts of hollow glass beads, 1 part of mannitol and 2 parts of polyether modified polysiloxane;

[0047] S2: stirring the water-based acrylic modified polyurethane resin at a speed of 20 r / min, adding mannitol first and then adding the remaining raw materials in component A in small amounts and multiple times during the stirring process, and after the feeding is completed, increasing the speed to 250 r / min and stirring for 5 minutes to obtain a composition A, which is sealed and stored for later use;

[0048] S3 weighs 15 parts of polyester fiber, 15 parts of titanium dioxide modified bamboo charcoal, 1 part of heat-shrinkable modified nanocellulose, 2 parts of sodium tripolyphosphate and 30 parts of deionized water; the polyester fiber has a diameter of 16 μm and a length of 310 μm;

[0049] S4 stirs deionized water at a speed of 200 r / min, and during the stirring process, sodium tripolyphosphate, heat-shrinkable modified nanocellulose, titanium dioxide modified bamboo charcoal and polyester fiber are added in sequence, with an interval of 1 min for each raw material. After the feeding is completed, the speed is increased to 250 r / min and stirred for 5 min to obtain a B composition, which is sealed and stored for later use.

[0050] The construction of heat shrink resistant waterproof coating includes the following steps:

[0051] The B composition was stirred at a speed of 20 r / min, and the A composition was added in small amounts several times during the stirring process. After the addition was completed, the speed was increased to 250 r / min and stirred for 2 minutes, and finally the speed was increased to 1000 r / min and stirred for 2 minutes to obtain a coating;

[0052] Apply the coating evenly on the surface of the heat shrink tube (the inner diameter of the heat shrink tube is 10mm, the thickness is 2mm, and the material is heat shrinkable polyethylene, the same below) with a coating thickness of 120μm; leave it at room temperature for 7 days and the construction is completed.

[0053] Example 2

[0054] The preparation of easily dispersible modified magnetic powder comprises the following steps:

[0055] Deionized water, ferrous chloride, ferric chloride and sericin were weighed in a weight ratio of 100:6.35:4.05:3.5 and stirred to obtain a mixed solution, which was kept stirred to prevent precipitation and aggregation; the pH of the mixed solution was adjusted to 12 and stirred at 60° C. for 4 hours; during stirring, the pH of the mixed solution was adjusted to 7 and then dried at 120° C. into a powder to obtain easily dispersible modified magnetic powder.

[0056] The method for preparing titanium dioxide modified bamboo charcoal comprises the following steps:

[0057] Titanium dioxide, dispersant and bamboo charcoal fiber are weighed according to a weight ratio of 7:3:100; water 10 times the total weight of titanium dioxide, dispersant and bamboo charcoal fiber is added, stirred evenly and filtered to obtain a pressed cake; the pressed cake is crushed and sieved to obtain titanium dioxide modified bamboo charcoal in powder form.

[0058] The preparation of heat-shrinkable modified nanocellulose comprises the following steps:

[0059] Nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol, glucomannan, 2,3-epoxypropyltrimethylammonium chloride and sodium carboxymethyl starch were weighed in a weight ratio of 4:1:5:1:1:1; nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol and glucomannan were mixed, and stirred at 60°C for 1 hour to obtain a primary mixed solution; 2,3-epoxypropyltrimethylammonium chloride was added to the primary mixed solution, and the solution was stirred at 60°C for 1 hour to obtain a secondary mixed solution; sodium carboxymethyl starch was added to the secondary mixed solution, and the solution was stirred at 50°C for 1 hour, and the excess ethylene glycol was washed until neutral, and the solution was filtered and dried to obtain heat-shrinkable modified nanocellulose.

[0060] The preparation of heat shrinkage resistant waterproof coating comprises the following steps:

[0061] S1 weighed 130 parts of waterborne acrylic modified polyurethane resin, 20 parts of quartz, 10 parts of easily dispersible modified magnetic powder, 10 parts of hollow glass beads, 3 parts of mannitol and 4 parts of polyether modified polysiloxane;

[0062] S2: stirring the water-based acrylic modified polyurethane resin at a speed of 30 r / min, adding mannitol first and then adding the remaining raw materials in component A in small amounts and multiple times during the stirring process, and after the feeding is completed, increasing the speed to 500 r / min and stirring for 10 minutes to obtain a composition A, which is sealed and stored for later use;

[0063] S3 weighs 20 parts of polyester fiber, 20 parts of titanium dioxide modified bamboo charcoal, 1.5 parts of heat-shrinkable modified nanocellulose, 4 parts of sodium tripolyphosphate and 40 parts of deionized water; the polyester fiber has a diameter of 27 μm and a length of 480 μm.

[0064] S4 stirs deionized water at a speed of 250 r / min, and during the stirring process, sodium tripolyphosphate, heat-shrinkable modified nanocellulose, titanium dioxide modified bamboo charcoal and polyester fiber are added in sequence, with an interval of 1 min for each raw material. After the feeding is completed, the speed is increased to 500 r / min and stirred for 10 min to obtain a B composition, which is sealed and stored for later use.

[0065] The construction of heat shrink resistant waterproof coating includes the following steps:

[0066] The B composition was stirred at a speed of 30 r / min, and the A composition was added in small amounts several times during the stirring process. After the addition was completed, the speed was increased to 500 r / min and stirred for 3 minutes, and finally the speed was increased to 1000 r / min and stirred for 3 minutes to obtain a coating;

[0067] Apply the coating evenly on the surface of the heat shrink tube with a coating thickness of 140μm; leave it at room temperature for 7 days and the construction is completed.

[0068] Example 3

[0069] The preparation of easily dispersible modified magnetic powder comprises the following steps:

[0070] Deionized water, ferrous chloride, ferric chloride and sericin were weighed in a weight ratio of 100:6.35:4.05:3.3 and stirred to obtain a mixed solution, which was kept stirred to prevent precipitation and aggregation; the pH of the mixed solution was adjusted to 12 and stirred at 60° C. for 4 hours; during stirring, the pH of the mixed solution was adjusted to 7 and then dried at 120° C. into a powder to obtain easily dispersible modified magnetic powder.

[0071] The method for preparing titanium dioxide modified bamboo charcoal comprises the following steps:

[0072] Titanium dioxide, dispersant and bamboo charcoal fiber are weighed according to a weight ratio of 5:3:100; water 10 times the total weight of titanium dioxide, dispersant and bamboo charcoal fiber is added, stirred evenly and filtered to obtain a pressed cake; the pressed cake is crushed and sieved to obtain titanium dioxide modified bamboo charcoal in powder form.

[0073] The preparation of heat-shrinkable modified nanocellulose comprises the following steps:

[0074] Nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol, glucomannan, 2,3-epoxypropyltrimethylammonium chloride and sodium carboxymethyl starch were weighed in a weight ratio of 4:1:5:1:1:1; nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol and glucomannan were mixed, and stirred at 60°C for 1 hour to obtain a primary mixed solution; 2,3-epoxypropyltrimethylammonium chloride was added to the primary mixed solution, and the solution was stirred at 60°C for 1 hour to obtain a secondary mixed solution; sodium carboxymethyl starch was added to the secondary mixed solution, and the solution was stirred at 50°C for 1 hour, and the excess ethylene glycol was washed until neutral, and the solution was filtered and dried to obtain heat-shrinkable modified nanocellulose.

[0075] The preparation of heat shrinkage resistant waterproof coating comprises the following steps:

[0076] S1 weighed 115 parts of waterborne acrylic modified polyurethane resin, 15 parts of quartz, 7 parts of easily dispersible modified magnetic powder, 7 parts of hollow glass beads, 1.5 parts of mannitol and 3 parts of polyether modified polysiloxane;

[0077] S2: stirring the water-based acrylic modified polyurethane resin at a speed of 25 r / min, adding mannitol first and then adding the remaining raw materials in component A in small amounts and multiple times during the stirring process, and after the feeding is completed, increasing the speed to 400 r / min and stirring for 8 minutes to obtain a composition A, which is sealed and stored for later use;

[0078] S3 weighs 17 parts of polyester fiber, 17 parts of titanium dioxide modified bamboo charcoal, 1.3 parts of heat-shrinkable modified nanocellulose, 3 parts of sodium tripolyphosphate and 35 parts of deionized water; the polyester fiber has a diameter of 17 μm and a length of 340 μm.

[0079] S4 stirs deionized water at a speed of 230 r / min, and during the stirring process, sodium tripolyphosphate, heat-shrinkable modified nanocellulose, titanium dioxide modified bamboo charcoal and polyester fiber are added in sequence, with an interval of 1 min for adding each raw material. After the addition is completed, the speed is increased to 230 r / min and stirred for 7 minutes to obtain a B composition, which is sealed and stored for later use.

[0080] The construction of heat shrink resistant waterproof coating includes the following steps:

[0081] The B composition was stirred at a speed of 25 r / min, and the A composition was added in small amounts several times during the stirring process. After the addition was completed, the speed was increased to 230 r / min and stirred for 2.5 min. Finally, the speed was increased to 1000 r / min and stirred for 2.5 min to obtain a coating;

[0082] Apply the coating evenly on the surface of the heat shrink tube with a coating thickness of 130μm; leave it at room temperature for 7 days and the construction is completed.

[0083] Example 4

[0084] The polyester fiber is obtained by mixing two types of fibers of equal weight, the first type having a diameter of 16 μm and a length of 310 μm, and the second type having a diameter of 27 μm and a length of 480 μm.

[0085] The remaining steps are the same as those in Example 3.

[0086] Comparative Example 1

[0087] The heat-shrinkable modified nanocellulose was replaced with cellulose of equal weight, and the remaining steps were the same as in Example 3.

[0088] Comparative Example 2

[0089] The easily dispersible modified magnetic powder was replaced with an equal weight of aluminum hydroxide, and the remaining steps were the same as in Example 3.

[0090] Comparative Example 3

[0091] The polyester fiber has a diameter of 24 μm and a length of 400 μm. The heat-shrinkable modified nanocellulose is replaced with cellulose of equal weight, and the remaining steps are the same as those in Example 3.

[0092] Heat shrinkage performance test

[0093] The heat shrinkable tubes obtained in Examples 1-4 and Comparative Examples 1-3 were sprayed with an alcohol burner for 3 weeks (0.5-1 s per week) to shrink the heat shrinkable tubes to a working shape, and then the coating attached to the heat shrinkable tubes was observed with the naked eye to see whether bubbling, wrinkles or cracks occurred and recorded in Table 1.

[0094] Table 1 Heat shrinkage performance test record

[0095]

[0096]

[0097] As can be seen from Table 1, when the present invention uses shorter / longer / long-short mixed polyester fibers (Examples 1-4), the heat shrinkage performance can still be maintained the same as that of the prior art (i.e., Comparative Example 3), and no cracking, wrinkling, or bubbling occurs during the heat shrinkage of the base surface. However, when the present invention lacks heat-shrinkable modified nanocellulose (Comparative Example 1), wrinkling is likely to occur. When the present invention lacks easily dispersible modified magnetic powder (Comparative Example 2), bubbling is likely to occur.

[0098] Waterproof test

[0099] Examples 1-4 were tested for water impermeability according to GB / T19250-2013. The results were all water impermeable.

[0100] The above embodiments and descriptions are only for illustrating the principles and best embodiments of the present invention. Without departing from the spirit and scope of the present invention, the present invention may be subject to various changes and improvements, all of which fall within the scope of the present invention to be protected.

Claims

1. A heat shrinkage resistant waterproof coating, characterized in that: The invention comprises the following raw materials in parts by weight: Component A: 100-130 parts of water-based acrylic modified polyurethane resin, 10-20 parts of quartz, 5-10 parts of easily dispersible modified magnetic powder, 5-10 parts of hollow glass beads, 1-3 parts of mannitol and 2-4 parts of polyether modified polysiloxane; Component B: 15-20 parts of polyester fiber, 15-20 parts of titanium dioxide modified bamboo charcoal, 1-1.5 parts of heat-shrinkable modified nanocellulose, 2-4 parts of sodium tripolyphosphate and 30-40 parts of deionized water; The method for preparing the easily dispersible modified magnetic powder comprises the following steps: Step 1: weigh deionized water, ferrous chloride, ferric chloride and sericin according to a weight ratio of 100:6.35:4.05:3-3.5 and stir and mix evenly to obtain a mixed solution and keep stirring; Step 2: Adjust the pH of the mixture to 12 and stir at 60°C for 4 hours; Step 3: Adjust the pH of the mixed solution to 7 during stirring and then dry it at 120°C into powder to obtain easily dispersible modified magnetic powder; The preparation method of titanium dioxide modified bamboo charcoal comprises the following steps: The first step is to weigh titanium dioxide, dispersant and bamboo charcoal fiber according to a weight ratio of 4-7:3:100; Step 2: Add 10 times the total weight of titanium dioxide, dispersant and bamboo charcoal fiber in water, stir evenly and filter to obtain a pressed cake; Step 3: crush and sieve the pressed cake to obtain titanium dioxide modified bamboo charcoal in powder form; The preparation method of the heat-shrinkable modified nanocellulose comprises the following steps: The first step is to weigh nanocellulose, 20wt% sodium hydroxide aqueous solution, ethylene glycol, glucomannan, 2,3-epoxypropyltrimethylammonium chloride and sodium carboxymethyl starch in a weight ratio of 4:1:5:1:1:1; Step 2: Mix nanocellulose, 20 wt% sodium hydroxide aqueous solution, ethylene glycol and glucomannan, and stir at 60° C. for 1 h to obtain a primary mixed solution; Step 3: Add 2,3-epoxypropyltrimethylammonium chloride to the primary mixed solution and stir for 1 hour at 60°C to obtain a secondary mixed solution; Step 4: add sodium carboxymethyl starch to the second mixed solution, stir at 50°C for 1 hour, wash with excess ethylene glycol until neutral, filter and dry to obtain heat-shrinkable modified nanocellulose.

2. The heat shrinkage resistant waterproof coating according to claim 1, characterized in that: The polyester fiber has a diameter of 15-30 μm and a length of 300-350 μm or 450-500 μm.

3. A method for preparing the heat shrinkage resistant waterproof coating according to claim 1, characterized in that: The following steps are involved: S1 weighs the water-based acrylic modified polyurethane resin, quartz, easily dispersible modified magnetic powder, hollow glass beads, mannitol and polyether modified polysiloxane in the formula amount of component A; S2: stirring the water-based acrylic modified polyurethane resin at a speed of 20-30 r / min, adding mannitol first and then adding the remaining raw materials in component A in small amounts and multiple times during the stirring process, and after the feeding is completed, increasing the speed to 250-500 r / min and stirring for 5-10 minutes to obtain a composition A, which is sealed and stored for later use; S3 weighs the polyester fiber, titanium dioxide modified bamboo charcoal, heat-shrinkable modified nanocellulose, sodium tripolyphosphate and deionized water in the B component; S4: Stir deionized water at a speed of 200-250 r / min, and add sodium tripolyphosphate, heat-shrinkable modified nanocellulose, titanium dioxide modified bamboo charcoal and polyester fiber in sequence during the stirring process, with an interval of 1 min for each raw material. After the feeding is completed, increase the speed to 250-500 r / min and stir for 5-10 min to obtain a B composition, which is sealed and stored for later use.

4. A construction method of the heat shrinkage resistant waterproof coating as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Stir the B composition at a speed of 20-30 r / min, and add the A composition in small amounts and multiple times during the stirring process. After the addition is completed, increase the speed to 250-500 r / min and stir for 2-3 minutes, and finally increase the speed to 1000 r / min and stir for 2-3 minutes to obtain a coating; Step 2: Apply the coating evenly on the surface of the heat shrink tube; Step three: Place at room temperature for 7 days and the construction is completed.

5. The construction method of the heat shrinkage resistant waterproof coating according to claim 4, characterized in that: The coating thickness is 100-150 μm.

Citation Information

Patent Citations

  • Modified titanium dioxide / bamboo charcoal composite material, preparation method thereof and method for preparing cigarette filter by adopting material

    CN102671663A

  • Preparation of novel magnetic nano-particle and method for separation of lysozyme from egg white

    CN103394338A